Development of Integrated Biodiversity Student Worksheets With Computational Thinking - Andriyani, Fitri; Suryanda, Ade; Ristanto, Rizhal Hendi (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2024)
Computational thinking is used in learning to improve problem-solving skills in Biology subjects. Classroom learning emphasizes students memorizing biological science concepts in problem-solving, resulting in students' computational thinking skills needing to be improved. So, efforts to overcome this so that students are actively involved in the learning process and to improve students' computational thinking skills in understanding biodiversity material are by providing teaching materials such as LKPD. This study combines the concept of biodiversity with computational thinking components in worksheets so that students can develop computational skills while understanding Biology concepts. This development research aims to develop student worksheets by integrating computational thinking into biodiversity material. This development research was conducted using the 4-D method through 4 stages: define, design, develop, and disseminate. Data was collected using a questionnaire instrument by two validators consisting of language experts, material experts, and teaching material experts, as well as a readability test instrument by three teachers and ten students in class X at SMAN 3 Depok. The results of this study are in the form of student worksheets, which were successfully developed and suitable for use in learning because they obtained a valid category based on assessments from validators and a highly valid category from biology teachers and students.